India’s pulse policy landscape and its implications for trade - Roy, Devesh; Boss, Ruchira; Pradhan, Mamata; Ajmani, Manmeet Singh (International Food Policy Research Institute, 2022)
The paper attempts to fill a knowledge gap by examining India’s pulse complex, consisting of production, consumption, and trade policies. India’s pulse policies are anchored in a cereal-centric farming system and prioritize national self-sufficiency as well as the mitigation of relative price increases in food. On the farmer side, government policy includes price support (a minimum support price [MSP]) for different pulses initially without procurement, but later backed by public procurement. The MSP plus procurement elicited a comparatively high supply response. Without procurement, the MSP worked only to anchor prices and benefit traders at the farmers’ expense. By not accounting for the needed risk premium (for a supply response) the MSP kept domestic production low. Even as the world’s largest importer of pulses, the scale of pulse imports in India have generally not been large enough to cool its markets and bring down domestic prices. Instantaneous supply adjustments by exporters in response to trade policy changes are difficult.